Clinical significance and prognostic value of femoral lymph node metastasis in FIGO stage III vulvar carcinoma. Issue 9 (September 2017) - Tu, H.; Sun, P.; Gu, H.F.; Zhang, X.K.; Huang, H.; Wan, T.; Liu, J.H.
Abstract: Objectives: To determine the clinical significance and prognostic value of femoral lymph node metastasis (FLNM) in patients with International Federation of Gynecology and Obstetrics (FIGO) stage III vulvar carcinoma. Methods: The medical records of patients with vulvar carcinoma who underwent inguinofemoral lymphadenectomy between 1990 and 2013 were retrospectively reviewed. Results: Of 66 patients with stage III vulvar carcinoma, 42 had superficial lymph node metastasis (SLNM) only and 24 had FLNM. Significantly higher rates of extracapsular invasion (P = 0.008), multiple nodal metastasis (P = 0.042), and advanced FIGO substage (P = 0.026) as well as a larger tumor diameter (≥4 cm, P = 0.023) and greater depth of invasion (≥5 mm, P = 0.020) were observed among patients with FLNM compared to those with SLNM only. After a median follow-up of 46 months (range, 6–172 months), 35 patients experienced relapse and 30 died from disease. The 5-year cancer-specific survival (CSS) rates were 70.1% and 30.8% for patients with SLNM only and FLNM, respectively (P = 0.001). In multivariate analysis, only FLNM was found to be an independent risk factor for reduced recurrence-free survival (RFS) and CSS among patients with stage III vulvar cancer (hazard ratio [HR] = 2.277, P = 0.037 for RFS; HR = 2.360, P = 0.042 for CSS). When the FLNM cases were considered together as stage IIIC, significant differences emerged in the RFS (P = 0.002) and CSS (P = 0.004) among the re-divided FIGO substages. Conclusions: FLNM represented an unfavorable status of node metastasis with a worse prognosis compared to that of SLNM alone, and this should be considered in a future FIGO staging system for vulvar cancer.